Menjelajahi Efektivitas Minyak Zaitun dalam Mencegah Luka Tekanan: Sebuah Ulasan Sistematis: Tinjauan Sistematik - Wijaya, Lorettha; Isabella, Maria Victoria; Yolanda, Rennie; Soeselo, Daniel Ardian; -, William; Cahyadi, Alius (Cermin Dunia Kedokteran, 2026)
Introduction: Pressure ulcers frequently occur in bedridden patients as a result of immobility and friction, causing delays in recovery and leading to complications. Natural skin care, including olive oil, have shown promising results in preventing ulcers. This paper aims to assessthe efficacy of olive oil in reducing the risk factors associated with pressure ulcers and preventing their occurrence in bedridden patients. Methods: A systematic review using PRISMA guidelines, examining studies from 2012 to 2025. All studies measuring the effect of oliveoil in preventing pressure ulcers in bedridden patients and calculating the risk using the Braden Scale Score were included. The RoB 2 and ROBINS-I quality assessment tools assessed the risk of bias. Results: Ten studies with a low risk of bias, comprising 662 participants, were included. Nine studies showed a preventive effect of pressure ulcers, while one study showed that pressure ulcers were still developing despite olive oil application. Conclusion: Olive oil is beneficial in reducing pressure ulcer risk factors and preventing pressure ulcers in bedridden patients.